Los Universos Lucidos : (El pabellón) - Clot, Manel; Galeria Fernando Alcolea, Barcelona; Galeria Antonio de Barnola, Barcelona; Galeria Antoni Estrany, Barcelona; Galeria Angels de la Mota, Barcelona; Galeria Sebastia Petit, Barcelona; Galeria Carles Poy, Barcelona (Barcelona : Galeria Fernando Alcolea, 1994)
Abad, Antoni ; Aballi, Ignasi ; Agut, Pep ; Canudas, Jordi ; Garau, Antoni ; Gomez, Susy ; Guerra, Carles ; Guillen-Balmes, Ramon ; Montalban, Begoña ; Palacin, Mabel ; Viaplan, Marc ; Ribalta, Jorge ; Roig, Ramon ; Rom, Joan ; Ruiz, Aureli ; Viaplana, Vincenç
Los Universos Lucidos (El Pabellón), Galeria Fernando Alcolea, Barcelona / Galeria Antonio de Barnola, Barcelona / Galeria Antoni Estrany, Barcelona / Galeria Angels de la Mota, Barcelona / Galeria Sebastia Petit, Barcelona / Galeria Carles Poy, Barcelona
boek